Loss of imprinting of IGF2 characterises high IGF2 mRNA-expressing type of fibroblast-like synoviocytes in rheumatoid arthritis. Issue 6 (24th June 2009) - Martin-Trujillo, Alejandro; van Rietschoten, Johanna G I; Timmer, Trieneke C G; Rodríguez, Francisco Milena; Huizinga, Tom W J; Tak, Paul P; Marsal, Sara; Ibrahim, Saleh M; Dijkmans, Ben A C; van der Pouw Kraan, Tineke C T M; Verweij, Cornelis L
Abstract : Objective: Increased expression of insulin-like growth factor 2 (IGF2) by fibroblast-like synoviocytes (FLS) was associated with low inflammatory synovium of patients with rheumatoid arthritis (RA). The aim of this study was to analyse whether the differential expression of IGF2, whose expression is normally restricted to one allele, is due to activation of the normally suppressed allele. Methods: IGF2 gene expression of RA FLS was quantified by quantitative real-time PCR. FLS heterozygous for a 3′-untranslated region IGF2 polymorphism were selected to measure the relative contribution of the allelic transcripts by allele-specific transcript quantification assay. Proliferation was determined by [ 3 H]thymidine incorporation. Results: IGF2 was shown to contribute to RA FLS proliferation. FLS could be classified in IGF2 high and IGF2 low-expressing cell lines. Allelic IGF2 transcript quantification analysis revealed that in part of the RA FLS the normally suppressed allele was activated, resulting in biallelic expression of the IGF2 gene. Biallelic expression was associated with increased levels of IGF2 mRNA production. Conclusion: The findings indicate that the imprinting status of IGF2 might underlie the increased expression of IGF2, which may contribute to autonomous growth of RA FLS of low inflammatory synovial tissues.